THE ROLE OF COGNITIVE PROCESSING STRATEGIES IN ENHANCING EFL LEARNERS’ READING EFFICIENCY - Saxatova Iroda Sunnatillayevna (Modern World Education: New Age Problems – New solutions, 2025)
This paper examines how cognitive strategies enhance EFL learners’ reading efficiency by supporting meaning construction, schema activation, and comprehension regulation. The analysis highlights predicting, inferencing, summarizing, elaboration, and monitoring as essential mechanisms that strengthen strategic reading development and promote deeper engagement with academic texts.